Chemical Composition and Biological Activities of Tunisian Cupressus arizonicaGreene Essential Oils. Issue 1 (January 2014) - Ismail, Amri; Mancini, Emilia; De Martino, Laura; Hamrouni, Lamia; Hanana, Mohsen; Jamoussi, Bassem; Gargouri, Samia; Scognamiglio, Mariarosa; De Feo, Vincenzo
Abstract The chemical composition of the essential oils obtained by hydrodistillation of leaves, stems, and female cones of Cupressus arizonicaGreene, grown in Tunisia, was studied by GC‐FID and GC/MS analyses. Altogether, 62 compounds were identified, 62 in the leaf oil, 19 in the cone oil, and 24 in the stem oil. The cone and stem oils were mainly composed by monoterpene hydrocarbons (96.6 and 85.2%, resp.). In the leaf oil, the total sesquiterpene fraction constituted 36.1% and that of the monoterpene hydrocarbons 33.8% of the total oil composition. The three oils were evaluated for their in vitro herbicidal activity by determining their influence on the germination and the shoot and root growth of the four weed species Sinapis arvensis L., Lolium rigidumGaudin, Trifolium campestreSchreb., and Phalaris canariensis L. At the highest doses tested (0.8 and 1.0 mg/ml), the leaf essential oil inhibited either totally or almost completely the seed germination and the shoot and root growth of S. arvensis and T. campestre. The oils were also tested for their antifungal activity; however, their effects on the fungal growth were statistically not significant.